Inhibition of Aberrant Activated Fibroblast‐Like Synoviocytes in Rheumatoid Arthritis by Leishmania Peptide via the Regulation of Fatty Acid Synthesis Metabolism - Jianling Su; Xuemei Fan; Yaoyao Zou; Guangtao Fu; Shiqi Feng; Xiaoxue Wang; Yongmei Yu; Lin Li; Zhenhua Bian; Rongrong Huang; Linmang Qin; Jiping Chen; et al. (Advanced Science)
Abstract The Leishmania homolog of receptors for activated C kinase (LACK) protein is derived from Leishmania parasites L. major. The polypeptide LACK156–173 has been shown to confer protection against murine autoimmune arthritis. Fibroblast‐like synoviocytes (FLSs) play a pivotal role in the synovial invasion and joint destruction observed in rheumatoid arthritis (RA). The study reveals that LACK156‐173 can inhibit the aggressive phenotype of RA‐FLSs by restoring dysregulated fatty acid synthesis metabolism. In RA‐FLSs, overexpression of fatty acid synthase (FASN) leads to excessive fatty acid accumulation, which in turn promotes mitochondrial fragmentation by enhancing phosphorylation at the ser616 site of dynamin 1‐like protein (DRP1). This process increases reactive oxygen species (ROS) production and activates the PI3K/mTOR/NF‐κB pathway, thereby facilitating the transition of RA‐FLSs to an aggressive inflammatory and bone‐damaging phenotype. LACK156‐173 is internalized into the cytoplasm via CAPN2‐mediated endocytosis, where it directly binds to FASN and inhibits its activity. The findings suggest that targeting the restoration of fatty acid metabolism could potentially alleviate synovial invasion and joint damage in RA. LACK156‐173 may therefore hold therapeutic promise for RA patients.